Differences between inter- and intra-group dynamics in knowledge transfer processes. Issue 4 (15th May 2017) - Nakauchi, Motohiro; Washburn, Mark; Klein, Kenji
Abstract : Purpose: Knowledge transfer (KT) processes are important for building and sustaining competitive advantages and dynamic capabilities. Prior research often treats KT processes as a firm-level capability, assuming knowledge flows uniformly within a firm. The purpose of this paper is to examine whether such a view is too simplistic because it ignores potential differences between inter-group and intra-group KT processes within a firm. Design/methodology/approach: The authors surveyed 137 software development professionals in a large Japanese electronics firm regarding co-workers who acted as critical sources of useful knowledge and the factors that affected KT within and across internal organizational boundaries. Using regression analysis, the authors test the extent to which factors such as the characteristics of the knowledge, the characteristics of the tie, and the characteristics of the network differentially affect KT within internal organizational boundaries vs across them. Findings: The authors find that factors such as the accessibility of the knowledge source, network density, and collective teaching all help in transferring knowledge, while knowledge tacitness inhibit such transfers, but that the effect of these properties varies significantly depending on whether KT occurs across group boundaries. Originality/value: Existing research on KT within firms tends to treat all such transfers as uniform, with little difference between the dynamics of within-group transfer and between-group transfer. This study establishes key differences in KT between and within organizational groups, demonstrating that managers need to consider internal boundaries when deploying tools and strategies for facilitating knowledge flows.